Controling an isolated oversaturated intersection in real time. Fuzzy logic approach. - Jovanović, Aleksandar D.; Kukić, Katarina S. (Vojnotehnički glasnik / Military Technical Courier, 2017)
In this paper we consider a problem of controling an oversaturated intersection in real time. We developed a mathematical model for solving the problem, based on fuzzy logic. The model can be applied to intersections characterized by oversaturated traffic flows. We compared this fuzzy logic approach to the "fixed time" controling of the oversaturated intersection. By “fixed time” we understood controlling based on the hystorical data about traffic flows. In the case of the oversaturated intersection considered in this paper, a classical approach of controlling in real time (“actuated time control”) gives the same solutions as “fixed time“ control. The criterion function for comparing solutions represents the control delay of all vehicles that pass through the intersection within a certain period of analysis. We tested these approaches on a “T” intersection, where the suggested model based on fuzzy logic generated solutions with less control delay in comparison to the “fixed time” model.